O-22 Prevalence and trends of medical end-of-life decisions in german-speaking Switzerland. (1st September 2015) - Faisst, Karin; Zellweger, U; Bopp, M; Schmid, M; Hurst, S; Bosshard, G
Abstract : Background: End-of-life medical decision-making is becoming more frequent. Reliable empirical data on what doctors do and how they decide in real end-of-life situations is scarce. Aims: The project aims to give an up-to-date assessment of the main features of medical end-of-life decision making practices in the German-speaking part of Switzerland; evaluate the changes in end-of-life decision making in the German-speaking part of Switzerland since 2001. Methods: We sampled approximately 5000 randomly selected deaths in the German-speaking part of Switzerland reported to the Swiss Federal Office of Statistics between July 31, 2013 and January 31, 2014. Physicians who signed the selected death certificates were sent a questionnaire. Results: The response rate was 63%. The first results indicate that the proportions of medical end-of-life decisions have not changed dramatically over the last decade. However compared to 2001 there was a remarkable increase of non-treatment decisions and terminal sedation. Although the rate of discussed decisions among competent patients slightly decreased, it can still be considered as high. Discussion: This is the first analysis of trends in an important field of medical decision-making in a German-speaking area. The results confirm the characteristics found in the first study in 2001 and implicate that non-treatment decisions are an important practice in Switzerland. Conclusion: These results on prevalence and trends of end-of-life decision-making of physicians in Switzerland contribute to an evidence-based discussion of a highly emotional topic.